Synergistic anti-angiogenic treatment effects by dual FGFR1 and VEGFR1 inhibition in FGFR1-amplified breast cancer. Issue 42 (18th October 2018) - Golfmann, Kristina; Meder, Lydia; Koker, Mirjam; Volz, Caroline; Borchmann, Sven; Tharun, Lars; Dietlein, Felix; Malchers, Florian; Florin, Alexandra; Büttner, Reinhard; Rosen, Neal; Rodrik-Outmezguine, Vanessa; et al.
Abstract FGFR1 amplification has been found in 15% of patients with breast cancer and has been postulated as a promising marker to predict response against FGFR inhibitors. However, early phase clinical trials of selective FGFR inhibitors demonstrated only limited efficacy inFGFR1 -amplified breast cancer patients. We found that BGJ398, an FGFR inhibitor, effectively inhibited phosphorylation of FGFR1 and MEK/ERK signaling inFGFR1- amplified breast cancer without affecting tumor cell proliferation. However, FGFR1 knockout inhibited tumor angiogenesis in vivo. We unraveled that FGFR1 regulates the secretion of the proangiogenic vascular endothelial growth factor (VEGF) in a MAPK-dependent manner. We further found that FGF-FGFR1 signaling induces an autocrine activation of VEGF-VEGFR1 pathway that again amplifies VEGF secretion via VEGF-VEGFR1-AKT signaling. Targeting both VEGFR1 and FGFR1 resulted in synergistic anti-angiogenic treatment effects in vivo. We thus postulate synergistic treatment effects in FGFR1/VEGFR1-positive breast cancer patients by dual targeting of FGFR and VEGFR.